Ekonomi Kreatif Guna Meningkatkan Perekonomian Melalui Masyarakat Kampung Adat - Nur Lidya Nurson; Solfema Solfema; Lili Dasa Putri (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2025)
Traditional villages can also be called nagari, hutan, marga and so on, are government units managed by indigenous people who have the right to manage certain areas and the lives of people in the traditional village environment. In various regions, traditional villages have different names, such as nagari, huta, marga and negeri. Traditional village communities are communities that live in a traditional customary law environment, they are known as people who love and uphold tradition. There are many things that can be developed into part of the creative economic activities of traditional village communities such as handicrafts making woven fabrics, woven cloth, wood carvings, and other craft products that contain cultural values. Development of typical food and drinks that have unique appeal and can be used as commercial products. ecotourism, natural and cultural tourism that utilizes the uniqueness of nature and the traditions of traditional villages, for example tourist villages or homestays that offer the experience of living in traditional villages. Performing arts present dance, music, or traditional rituals that are not only entertaining, but also become a medium of cultural education for tourists. All of these will be activities that support the progress of the creative economy.